Penguatan Kohesi Sosial Melalui Peran Aktif Masyarakat Seberang Palinggam - Junaidi Indrawadi; Isnarmi Moeis; Maria Montessori; Wirdanengsih Wirdanengsih; Fatmariza Fatmariza; Arieska Dwi Asmil; Hafsyari Hafsyari (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
In fact, each ethnic group that is scattered in Indonesia has a natural tendency to create social cohesion internally and externally. This can be seen from the relationships, interactions, and integration processes that are built within a certain period of time as one of the impacts arising from assimilation. Assimilation is an important note for heterogeneous communities full of differences to respect each other's differences through an attitude of tolerance, cooperation, and the application of various teachings of unity that have been believed to be passed down through tradition. The efforts in question have been seen in the multi-ethnic and multi-religious Seberang Palinggam community. For this reason, this paper will analyze more deeply the efforts made by the Seberang Palinggam community in strengthening their social cohesion. This analysis was carried out by collecting data in the form of observations, documentation, and interviews related to the wisdom possessed by local communities and interactions in the social life of their citizens. The results show that strengthening social cohesion arises from strengthening the traditions of each tribe which basically has the principles of 'unity' and 'brotherhood'. This principle can be seen from the tradition of Baralek Basamo, symbolic of the Bulek Chicken, Selaju Sampan Dayuang Palinggam, and others.